EFFECTS OF ENVIRONMENTAL STRESSORS ON SOCIAL HIERARCHIES IN PRIMATES (International Journal of Food and Nutritional Sciences, 2023)
The social hierarchies of primates are integral to the organization and functioning of their groups, influencing access to resources, mating opportunities, and social interactions. Environmental stressors, such as food scarcity, habitat degradation, climate change, predation pressure, and human interference, have profound effects on these hierarchies, often leading to shifts in social dynamics and group cohesion. This study explores the impact of environmental stressors on primate social structures and behavior. When primates are subjected to environmental stressors, their established social hierarchies can become destabilized. Food scarcity, for instance, intensifies competition for resources, with dominant individuals exerting tighter control over food access, often leading to increased aggression and social tension. Subordinate individuals, with limited access to resources, may experience heightened stress, which can affect their health and reproductive success. Similarly, changes in climate and habitat fragmentation force primates to adapt to new and often less predictable environments, which can lead to reorganization within groups and shifts in power dynamics.